Hazard Identification, Risk Assessment and Risk Control (HIRARC) Accidents at Power Plant - Ahmad Asmalia Che; Mohd Zin Ida Nianti; Othman Muhammad Kamil; Muhamad Nurul Huda (MATEC Web of Conferences, 2016)
Power plant had a reputation of being one of the most hazardous workplace environments. Workers in the power plant face many safety risks due to the nature of the job. Although power plants are safer nowadays since the industry has urged the employer to improve their employees’ safety, the employees still stumble upon many hazards thus accidents at workplace. The aim of the present study is to investigate work related accidents at power plants based on HIRARC (Hazard Identification, Risk Assessment and Risk Control) process. The data were collected at two coal-fired power plant located in Malaysia. The finding of the study identified hazards and assess risk relate to accidents occurred at the power plants. The finding of the study suggested the possible control measures and corrective actions to reduce or eliminate the risk that can be used by power plant in preventing accidents from occurred